Pengembangan Media Pembelajaran Game Edukasi Genially Berbasis Problem Based Learning Pada Materi Asam Basa : Penelitian - Rezi Putri Mayori; Yusnidar; Afrida (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop an educational game-based learning media using Genially integrated with Problem-Based Learning (PBL) on acid-base material, as well as to determine its feasibility, teachers' evaluations, and students' responses toward the developed media.The research employs the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The assessment instruments used in this study consist of interview guidelines and questionnaires. The data analysis techniques involve qualitative analysis of comments and suggestions, and quantitative analysis through mean scores and percentages.The result of the study is a product in the form of Genially-based educational game media integrated with Problem-Based Learning on acid-base material. The media was validated by subject matter experts and media experts with average scores of 4.26 and 4.55, respectively, both categorized as